EKSPERIMENTASI METODE PEMBELAJARAN PROBLEM POSING DENGAN PENDEKATAN CTL PADA MATERI BANGUN DATAR DITINJAU DARI TINGKAT INTELEGENSI SISWA KELAS VII SMP NEGERI SE-KABUPATEN PURWOREJO TAHUN PELAJARAN 2012/2013 - Imswatama, Aritsya; Mardiyana, Mardiyana; Usodo, Budi (Jurnal Pembelajaran Matematika, 2013)
Abstract: The aim of the research was to determine the effect of learning methods on mathematics achievement viewed from the student intelligence level. The learning methods compared were problem posing with CTL approach, problem posing and conventional. The type of the research was quasi experimental research. The population was all of students in the seventh grade of Junior High School in Purworejo in the academic year of 2012/2013. The sample of this research was taken by using stratified cluster random sampling. The sample was consisted of 177 students with 90 students in the first experiment class, 95 students in the second experiment class, and 92 students in the control class. The data ofÂ  the research were gathered through documentation and test. The result of research showed that: (1) studentsâ learning achivement by using problem posing learning method with CTL approach was better than studentsâ learning achivement by using problem posing method and conventional learning, and studentsâ learning achivement by problem posing learning method was same as conventional learning method, (2) mathematics achievement of students with high intelligence level was better than that of students with medium and low intelligence level, and mathematics achievement of students with medium intelligence level was better than that of students with low intelligence level, (3) in learning by using problem posing learning method with CTL approach, the level of intelligence had the same effect in studentsâ learning achievement, in learning by using problem posing method, students with high intelligence level had performance as good as the students with medium intelligence level and were better than the students with low intelligence level, in learning by using conventional learning, students with high intelligence level had better learning achivement than students with medium intelligence level and low intelligence level, and learning achievement of students with medium intelligence level was the same as students with low intelligence level, (4) at the level of studentsâ intelligence with high, medium and low, problem posing learning method with CTL approach, problem posing learning method and conventional method produced the same effect in learning achievement. Keywords: problem posing with CTL aproach, problem posing, learning achievement, intelligence level.